Clinical and Angiographic Follow Up of Patients Undergoing SPECT MPI using Sodium-Iodide (Na-I) Camera Versus High Efficiency Cadmium-Zinc-Telluride (HE CZT) Camera With A Low Dose Protocol - Rawal, Harsh; Mahajan, Sugandhi; Patel, Ravi; Memon, Waqas; Maini, Rohit; Kabir, Christopher; Mehta, Sanjay S (Cardiology and Cardiovascular Medicine, 2019)
Background: Newly introduced CZT camera has shown to reduce radiation without affecting image quality. Our goal was to assess the results of nuclear testing using the new CZT camera and traditional Na-I camera in comparison with standard coronary angiography. Methods: All patients referred for nuclear stress testing using the CZT camera in the first quarter of 2015 were enrolled. Angiography was performed for abnormal scans or persistent symptoms. These patients were compared to the patients who underwent Na-I SPECT MPI in the first quarter of the previous year using the standard protocol and subsequent cardiac catheterization. Results: 162 patients underwent cardiac catheterization in the first quarter of year 2015 compared to 145 patients from the previous year. CZT camera had a higher sensitivity of 96.8 compared with 87.6 for the Na-I camera (P-value=0.011). The accuracies of the two cameras were 78.6 and 77.2 respectively. Conclusion: The accuracy of identifying obstructive CAD using the CZT camera approaches 78.6% irrespective of age & sex compared to 77.2% using the Na-I camera. MPI with low dose protocol using the CZT camera is reliable in diagnosing CAD with the benefit of radiation reduction (approx. 48-50%) and reduced scan time without statistical difference in accuracy.